DEVELOPMENT AND VALIDATION OF ANALYTICAL METHOD FOR QUANTIFICATION OF ACETIC ACID CONTENT IN AMLODIPINE BESYLATE - Haque, S. K. Manirul; Ahmad, Ayman (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: To develop and validate a simple and accurate cost-effective titrimetric method according to International Conference Harmonization (ICH) guidelines for acetic acid content in Amlodipine Besylate. Methods: The titration based on general acid-base reaction to form water and salt. Sodium hydroxide act as a strong base and titrated against weak acid (acetic acid). Phenolphthalein used as an indicator and colorless to pink is the endpoint. Sodium hydroxide is standardized with primary standard potassium hydrogen phthalate. Results: The method was linear in the range of 0.75 to 30.25 μg/ml with a correlation coefficient 0.9999. Limit of detection (LOD) and limit of quantitation (LOQ) value were found to be 0.61 and 1.85 μg/ml, respectively. The percentage recovery (98.20–99.97%) and percentage relative standard deviation (%RSD) is less than 2% within the acceptable limit of ICH guidelines. The robustness and ruggedness results were excellent. Method is accurate and precise, no interference from excipients. Conclusion: A new analytical titrimetric method was developed and validated as per ICH guidelines for the determination of acetic acid content in amlodipine. This proposed method applied for routine analysis of acetic acid content in bulk and pharmaceutical formulations of amlodipine besylate.